Instrumentation challenges of a pushbroom hyperspectral imaging system for currency counterfeit applications - Lim, Hoong-Ta (2018)
Hyperspectral imaging allows the intensity of narrow and adjacent spectral bands over a large spectral range to be recorded, giving rich spectral information for each pixel in the imaged region. The spectral characteristics of each point in the imaged region can thus be detected, which is useful for quantification and classification. Hyperspectral imaging has been used in many applications such as remote sensing, quality assessment of agro-food products, biomedical imaging and document counterfeit application. This paper presents a pushbroom spatial-scanning imager, which gives a higher spectral resolution over a broad spectral range. Although a spatial-scanning imager may be slower due to the need to perform mechanical scanning, such a high spectral resolution is especially important in applications where the capability to perform classification is much more important than speed. The application of this system is demonstrated for currency counterfeit detection applications. The high spectral resolution of a pushbroom imager is able to capture fine spectral details of the samples used in this research, providing important information required for classification. Using this technique, the reflectance is acquired from specific regions of a genuine and counterfeit note. The spectra of the same region from both notes are then compared to distinguish and delineate the differences between them. The spectrum acquired from a genuine note can then be used as a reference from which future comparison can be based upon for identifying currency counterfeit and related relevant applications.